2016
DOI: 10.1016/j.jmarsys.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Diapycnal diffusivity in the core and oxycline of the tropical North Atlantic oxygen minimum zone

Abstract: MotivationDiapycnal diffusivity plays an important role in the ventilation of the Eastern Tropical North Atlantic (ETNA) Oxygen Minimum Zone (OMZ). Studies by Fischer et al. (2013), Banyte et al. (2012) and the synthesis by Brandt et al. (2015) found that diapycnal mixing contributes up to 20%, locally up to 30%, to the oxygen supply in the OMZ. Diapycnal diffusivity in the core and oxycline of the tropical North Atlantic Oxygen Minimum Zone SFB 754This comparatively high contribution to the oxygen supply f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Steinfeldt et al, 2015): (Osborn, 1980), where is stratification and Γ is the mixing efficiency for which a value of 0.2 was used. The use of this value has recently shown to yield good agreement between turbulent eddy diffusivities determined from microstructure measurements and from tracer release experiments performed in our study region (Köllner et al, 2016). The 95% confidence intervals for station-averaged K ρ values were determined from Gaussian error propagation following Schafstall et al (2010).…”
Section: Turbulence Measurements and Vertical Flux Calculationsmentioning
confidence: 73%
“…Steinfeldt et al, 2015): (Osborn, 1980), where is stratification and Γ is the mixing efficiency for which a value of 0.2 was used. The use of this value has recently shown to yield good agreement between turbulent eddy diffusivities determined from microstructure measurements and from tracer release experiments performed in our study region (Köllner et al, 2016). The 95% confidence intervals for station-averaged K ρ values were determined from Gaussian error propagation following Schafstall et al (2010).…”
Section: Turbulence Measurements and Vertical Flux Calculationsmentioning
confidence: 73%
“…The strongest poleward flow is observed during the relaxation period between May and July when alongshore, upwelling-favorable winds weaken but wind stress curl is at its maximum (Klenz et al, 2018). During the upwelling season in boreal winter, the circulation more closely resembles the classical eastern boundary circulation regime, with a weak PUC flowing beneath an equatorward coastal jet (Klenz et al, 2018;Kounta et al, 2018). At deeper levels (300-500 m depth), flow was found to be equatorward during both seasons.…”
Section: Oceanographic Settings Of the Study Areamentioning
confidence: 93%
“…The coefficients of the horizontal and the vertical eddy diffusion are chosen based on previous observational studies. We use a vertical diffusivity of k z = 10 −5 m 2 /s (Banyte et al, 2012;Fischer et al, 2013;Köllner et al, 2016). Hahn et al (2014) suggested a meridional diffusivity k y of 500-1,400 m 2 /s between 100 and 300 m depth.…”
Section: 1029/2018jc014760mentioning
confidence: 99%